Epidemiology and Clinical Management of Early Childhood Caries in Israel - Shmueli, Aviv; Moskovitz, Moti; Halperson, Elinor; Ram, Diana; Fux-Noy, Avia (Frontiers in Public Health, 2019)
Abstract: Aim: The aim of the present review is to describe, the current status of Ecc - early childhood caries in Israel, in aspects of epidemiology, prevention and management. Background: ECC is a prevalent health problem in Israel. The decayed, missing and filled teeth index was reported as 2.72 in 1992 and 2.56 in 2016 (1). A number of preventive programs are described in the review; however, at the national level, a preventive program is lacking. In 2010, paediatric dental service became part of the national health services. Currently, by law, every child in Israel is eligible to receive dental treatment. Conclusion: Ecc is prevalent in Israel, although proportion of restored teeth has increased. Epidemiological Investigations in the field of Ecc in Israel should be performed.